2018
DOI: 10.1002/adma.201705942
|View full text |Cite
|
Sign up to set email alerts
|

Realizing zT of 2.3 in Ge1−xySbxInyTe via Reducing the Phase‐Transition Temperature and Introducing Resonant Energy Doping

Abstract: GeTe with rhombohedral-to-cubic phase transition is a promising lead-free thermoelectric candidate. Herein, theoretical studies reveal that cubic GeTe has superior thermoelectric behavior, which is linked to (1) the two valence bands to enhance the electronic transport coefficients and (2) stronger enharmonic phonon-phonon interactions to ensure a lower intrinsic thermal conductivity. Experimentally, based on Ge Sb Te with optimized carrier concentration, a record-high figure-of-merit of 2.3 is achieved via fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
190
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(202 citation statements)
references
References 51 publications
5
190
1
4
Order By: Relevance
“…Hong et al reported a peak zT value higher than 2 at ≈580 K. From ≈650 to ≈800 K, the peak zT values of GeTe‐based thermoelectric materials are higher than 1 . Further studies have enhanced the peak zT values of GeTe‐based thermoelectric materials to a level higher than 2 . Under this temperature range (from ≈650 to ≈800 K), other p‐type thermoelectric materials, such as SnSe and higher manganese silicide have also drawn extensive research interests due to either low cost or high performance.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al reported a peak zT value higher than 2 at ≈580 K. From ≈650 to ≈800 K, the peak zT values of GeTe‐based thermoelectric materials are higher than 1 . Further studies have enhanced the peak zT values of GeTe‐based thermoelectric materials to a level higher than 2 . Under this temperature range (from ≈650 to ≈800 K), other p‐type thermoelectric materials, such as SnSe and higher manganese silicide have also drawn extensive research interests due to either low cost or high performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] Therefore, many previous studies for improving thermoelectric GeTe focus on optimizing the carrier concentration. [ 39–45 ] An obvious solution is doping of elements acting as electron donors to decrease the hole carrier concentration. For example, Bi and Sb have been reported to be effective donors to decrease the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…A very high zT of 2.3 has been reported in Sb and In co-doped β-GeTe owning to the superior electronic properties and low κ l . 13 It is suggested that the phase transition from the lowsymmetry rhombohedral α-GeTe to the high-symmetry rocksalt β-GeTe plays a crucial role in enhancing thermoelectric efficiency through converging band pockets and suppressing κ l . 2,12,13 Therefore, it is fundamentally important to understand the lattice dynamics and thermal transport in β-GeTe, insight into which may enable further reduction of κ l and enhancement of zT .…”
mentioning
confidence: 99%
“…Motived by this point, we perform firsta) Electronic mail: yxia@anl.gov b) Electronic mail: mchan@anl.gov arXiv:1807.08012v2 [cond-mat.mtrl-sci] 6 Sep 2018 principles-based calculations of lattice dynamics and thermal transport properties of β-GeTe at 800 K, near the temperature of optimal experimental thermoelectric performance. 13 To resolve the imaginary phonon modes, we present an effective scheme to account for temperature effect by explicitly including anharmonicity up to 4th order, with a particular focus on temperature-induced anharmonic phonon renormalization (PRN) and four-phonon scattering. Phonon dispersions and atom-projected densities of states for rocksalt β-GeTe computed at 0 K (a) and 800 K (b), respectively.…”
mentioning
confidence: 99%